Symbiotic Enlightenment: Exploring the Fascination of Biology Education Students with Religion Studies in an Academic Tapestry - Tesa Ulandari; Dharma Ferry; Albertos Damni (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the Study: This study aims to evaluate the interest of biology students in attending general education courses, specifically religious subjects, while exploring the impact of various factors such as gender, academic background, and extracurricular involvement. By doing so, it seeks to better understand how these factors influence students' engagement in interdisciplinary education. Methodology: The research adopts a mixed-methods approach. It begins with quantitative analysis, employing descriptive statistics to assess general interest levels, followed by qualitative validation through interviews with seven selected informants. The study population consists of 131 active biology students in the 2023/2024 academic year, with a final sample of 100 after data cleaning. The sampling method used was total sampling to ensure broad representation. Principal Findings: The findings reveal a variety of interest levels among biology students in religious subjects, with no significant differences based on gender, academic semester, high school major, or extracurricular involvement in religious activities or organizations. However, the school of origin emerged as a significant factor, indicating that students' previous educational experiences play a crucial role in shaping their engagement with religious subjects. Novelty/Originality of this Study: This research introduces a novel perspective by uncovering the influence of a student’s educational background specifically, their school origin on their interest in interdisciplinary religious education. It offers new insights into how prior schooling experiences contribute to shaping students’ academic and personal interests, particularly within the context of general education courses, thus providing valuable implications for curriculum design in higher education.